Protective effect of erdosteine metabolite I against hydrogen peroxide-induced oxidative DNA-damage in lung epithelial cells - Marabini, Laura; Calò, Rossella; Braga, Pier Carlo (Arzneimittelforschung, 2011)
It has been shown that the mucolytic agent erdosteine (N-carboxymethylthio-acetyl-homocysteine thiolactone, CAS 84611–23–4) has anti-inflammatory and anti-oxidant properties, and an active metabolite I (MET I) containing pharmacologically active sulphydryl group has been found to have a free radical scavenging activity.The aim of this study was to assess the ability of erdosteine metabolite I to protect A549 human lung adenocarcinoma cell against hydrogen peroxide (H2O2)-mediated oxidative stress and oxidative DNA damage.When A549 cells were pre-treated with the active metabolite I (2.5–5–10 µg/ml) for 10–30 min and then exposed to H2O2 (1–4 mM) for two additional hours at 37 °C, 5% at CO2, the intracellular peroxide production, reflected by dichloro-fluorescein (DCF) fluorescence, decreased in a concentration-dependent manner. Furthermore, using a comet assay as an indicator for oxidative DNA damage, it was found that the metabolite I prevented damage to cells exposed to short-term H2O2 treatment.The data suggest that this compound is effective in preventing H2O2-induced oxidative stress and DNA damage in A549 cells. The underlying mechanisms involve the scavenging of intracellular reactive oxygen species (ROS).
Keywords: A549 cells; Anti-oxidant activity; DNA damage; Erdosteine metabolite I; Genotoxicity